Financial tools of investment activity stimulation in modern conditions - E. V. Dmitrieva (Путеводитель предпринимателя)
Stimulation of investment activity of the enterprises demands the corresponding set of financial instruments (budgetary funds, the credits, depreciation charges, profit, the raised funds, etc.) and their effective combination and use according to requirements of development of economy of the state.